IoT Innovations in Libraries: Transforming Services and Accessibility (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The advent of the Internet of Things (IoT) has ushered in a new era of innovation and transformation in libraries worldwide. "IoT Innovations in Libraries: Transforming Services and Accessibility" delves into the exciting realm of IoT technologies and their profound impact on modern library services and accessibility. In an age where digitalization and connectivity are paramount, this paper explores how libraries are embracing IoT to revamp their offerings. From smart shelves that optimize collection management to sensor-equipped spaces that enhance user experiences, this comprehensive guide showcases a myriad of IoT applications tailored to the library ecosystem. Through real-world case studies and best practices, readers will gain insights into how IoT is redefining library services. Discover how IoT-enabled systems facilitate seamless resource tracking, personalized recommendations, and real-time data analytics, empowering librarians to make informed decisions and offer unparalleled support to patrons. Accessibility is a core focus throughout the book, as IoT technologies open doors to a more inclusive library experience. Learn how IoT-driven assistive devices and smart navigation tools are breaking down barriers for individuals with disabilities, ensuring that libraries are welcoming and accommodating to all. It emphasizes the importance of safeguarding user privacy while harnessing the power of IoT for the betterment of library services